Proceedings of the 2nd biennial South African conference on spirituality and healthcare - De la Porte, André; Joubert, Nicolene; Oberholzer, Annemarie (Cambridge Scholars Publishing, 2018)
Illness causes an existential crisis for people as it confronts them with the fragility, vulnerability and finitude of the human condition. Serious illness and hospitalisation can be challenging and life-changing experiences, especially in a context with poor resources and limited support. Healthcare workers meet patients in this space of disarray. Human qualities, such as faith, hope and compassion become crucial aspects of care. Patients' responses to these qualities highlight the importance of spirituality as part of holistic care, not only for the patients and their families, but also for.